PENGARUH PENDIDIKAN KESEHATAN MELALUI MEDIA LEAFLET TERHADAP SIKAP REMAJA PUTRI TENTANG GENITALIA HYGIENE SAAT MENSTRUASI DI SMP NEGERI 1 MAKASSAR - Ernawati, Ernawati; Praditia, Yoan Putri; Subriani, St.; Qodri, Nurul (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan Pelamonia, 2025)
Background: Adolescence is defined as a significant transition period from childhood to adulthood, during which rapid physical and mental growth and development. Changes in the adolescent body are caused by the growth of reproductive organs or sex organs. Therefore, it is hoped that adolescents have the ability to maintain their health so they can face family life with healthy reproduction, especially for adolescent girls. The purpose of this study was to determine the effect of health education through leaflets on the attitudes of adolescent girls about genital hygiene during menstruation at SMP Negeri 1 Makassar. The method used in this study was an experimental one with a pre-post test design with a sample of 40 respondents, with the sampling technique being total sampling. Data collection used questionnaires (pre and post tests). Data analysis used the Wilcoxon Sign Rank test. The results showed that there was an effect of health education on the attitudes of adolescent girls about genital hygiene during menstruation with p = 0.000 so that Ha was accepted and Ho was rejected, meaning there was an effect of health education through leaflets on the attitudes of adolescent girls about genital hygiene during menstruation.